Development of Pisa 2015 Based Chemical Literacy Assessment Instrument For High School Students - Fika Aning Tiara; Oktavia Sulistina (Universitas Negeri Malang, 2021)
This study aims to develop valid and reliable chemical literacy assessment instruments based on PISA 2015. The development procedures carried out were 1) research and information collecting, 2) planning, 3) development preliminary form of product, 4) preliminary field testing, and 5) main product revision. Instrument of development result was validated(content validity and empirical validity). Content validity assessment data was obtained from the validity test results from two chemistry lecturers. Empirical validity test data were acquired from68 grade XI students as test subjects who came from five high schools in Malang. An empirical validity test was used to obtain the level of validity, reliability, discrimination index, difficulty level, and effectiveness of distractors of the items developed in the instrument. The instrument of development results consisted of 20 multiple choice items and 4 attitude questionnaires. The results of the content validity test indicated a valid instrument (the average score for the aspects of substance, construction, and language was 83.9). The results of the empirical validity test showed that multiple-choice items had a correlation value of 0.37-0.77, categorized as valid, and the reliability value was 0.86, classified as highly reliable. The discrimination index obtained was five items ranked as sufficiently good and 15 items categorized as good, while five items classified as easy item, 14 moderate items, and one difficult item, all distractors were functioning. The empirical validity test results in the form of an attitude questionnaire showed a correlation value of 0.65-0.69, so they were valid, and the reliability value was 0.59, classified as quite high criteria. Instrument development results proved to be valid and reliable, so it is feasible to be used to measure students' chemical literacy skills.ReferencesAmerican Association for the Advancement of Science (AAAS). (1993). Benchmarks for science literacy: a project 2061 report. New York: Oxford University Press.Arikunto, S. (1993). Dasar-Dasar Evaluasi Pendidikan. Jakarta: Bumi Aksara.Bond, D. (1989). In Pursuit of Chemical Literacy: A Place for Chemical Reactions. Journal of Chemical Education, 66(2), 157.Celik, S. (2014).Chemical Literacy Levels of Science And Mathematics Teacher Candidates. Australian Journal of Teacher Education, 39(1), 1 – 15Cigdemoglu, C., & Geban, O. (2015). Improving Students' Chemical Literacy Level on Thermochemical And Thermodynamics Concepts through Context-Based Approach. Chemistry Education Research And Practice, 16, 302 – 317.Cigdemoglu, C., Arslan, H. O., & Cam, A. (2017).Argumentation to Foster Pre-Service Science Teachers' Knowledge, Competency, And Attitude on The Domains of Chemical Literacy of Acids And Bases. Chemistry Education Research And Practice, 18(2), 288 – 303.Direktorat Pembinaan SMA. (2017). Panduan Penilaian oleh Pendidik dan Satuan Pendidikan Sekolah Menengah Atas. Jakarta: Kementerian Pendidikan dan Kebudayaan RI.Kohen, Z., Herscovitz, O., & Dori, Y. J. (2020). How to Promote Chemical Literacy? Online Question Posing And Communicating With Scientists. Chemistry Education Research And Practice, 21(1), 250 – 266Mudiono, A. (2016). Keprofesionalan Guru dalam Menghadapi Pendidikan di Era Global. Makalah disajikan dalam Seminar Nasional, Jurusan KSDP FIP UM, Malang 25 September.Mumba, F., & Hunter, W. J. F. (2009). Representative Nature of Scientific Literacy Themes in A High School Chemistry Course: The Case of Zambia. Chemistry Education Research And Practice, 10(3), 219 – 226.Naganuma, S. (2017). An Assessment of Civic Scientific Literacy in Japan: Development of A More Authentic Assessment Task And Scoring Rubric. International Journal of Science Education, Part B, 7(4), 301 – 322Norris, S. P., & Philip, L. M. (2003). How literacy in its fundamental sense in central to scientific literacy. Science Education, 87(2), 224 – 240.Organisation for Economic Co-operation and Development (OECD). (2016). PISA 2015 Assessment And Analytical Framework: Science, Reading, Mathematic And Financial Literacy. Paris: OECD PublishingOrganisation for Economic Co-operation and Development (OECD). (2018). PISA 2018 Result Combined Executive Summaries Volume I, II, & III. Paris: Organisation for Economic Co-operation and Development.Osborne, J. F. (2010). Arguing to Learn in Science: The Role of Collaborative, Critical Discourse. Science, 328(5977), 463 – 466Rahayu, S. (2014). Menuju Masyarakat Berliterasi Sains: Harapan dan Tantangan Kurikulum 2013. Makalah disajikan dalam Seminar Nasional Kimia dan Pembelajarannya, Jurusan Kimia FMIPA UM, Malang 6 September.Rahayu, S. (2017). Mengoptimalkan Aspek Literasi dalam Pembelajaran Kimia Abad 21. Makalah disajikan dalam Seminar Nasional Kimia, Jurusan Pendidikan Kimia FMIPA UNY, Yogyakarta, 14 Oktober.Riduwan. (2011). Belajar Mudah Penelitian: untuk Guru-Karyawan, dan Peneliti Pemula. Bandung: AlfabetaRiduwan. (2013). Dasar-Dasar Statistika. Bandung: AlfabetaShe, H. C., Stacey, K., & Schmidt, W. H. (2018).Science And Mathematics Literacy: PISA for Better School Education. International Journal of Science And Mathematics Education, 16(1), 1 – 5Shwartz, Y., Ben-Zvi, R., & Hofstein, A. (2005). The Importance of Involving High-School Chemistry Teachers in The Process of Defining the Operational Meaning of Chemical Literacy. International Journal of ScienceEducation, 27(3), 323 – 344.Thummathong, R., & Thathong, K. (2016). Construction of A Chemical Literacy Test for Engineering Students. Journal of Turkish Science Education, 13(3), 185 – 198.United Nations Environment Programme (UNEP). (2012). 21 Issues for the 21st Century: Result of the UNEP Foresight Process on Emerging Environmental Issues. Nairobi, Kenya: United Nations Environment Programme.Vogelzang, J., Admiraal, W. F., & van Driel, J. H. (2020). Effects of Scrum Methodology on Students' Critical Scientific Literacy: The Case of Green Chemistry. Chemistry Education Research And Practice, 21(3), 940 – 952.World Economic Forum (WEF). (2016). New Vision for Education: Fostering Social And Emotional Learning through Technology.